First report of Ophidascaris spp. (Class: Nematode) Infection in Wild-Caught Javanese Keelback Water Snake (Fowlea melanzostus) in Banyuwangi District - Yudhana, Aditya; Salsabila Putri, Elma; Angga Prastiya, Ragil; Nurwartanti Yunita, Maya; Agustono, Bodhi; Ayu Wibawati, Prima (Universitas Airlangga, 2024)
The javanese keelback water snake (Fowlea melanzostus) is a semi-aquatic reptile that often found in Indonesia and endemic to Java island. Water tiger snakes are usually kept as exotic pets. Wild caught javanese keelback water snakes have risks of spreading several disease agents that can be zoonotic, which is nematodiasis caused by Ophidascaris spp. This study aims to determine the prevalence level of Ophidascaris spp. infections in javanese keelback water snakes from Banyuwangi district. This study used a descriptive method with accidental sampling. The total sample in this study was 33 wild-caught javanese keelback water snakes. The identification method used is snake samples that have been collected are then euthanized and necropsied to check for nematode infections in the subcutan, muscular, and visceral part. The result showed that 28 samples were positive for nematode infection and 5 samples were negative with a prevalence rate of 84.84%. The nematodes that have been identified come from the genus Ophidascaris spp. Therefore, further research is needed to determine the incidence of nematode transmission in other wild caught snakes in Indonesia.